2015
DOI: 10.3109/0284186x.2015.1094186
|View full text |Cite
|
Sign up to set email alerts
|

Risk of non-sentinel node metastases in patients with symptomatic cancers compared to screen-detected breast cancers

Abstract: (182) in the sentinel node. Patients were cross-checked in the Danish Quality Database of Mammography Screening and 481 patients were identified as screen-detected cancers. The remaining 474 patients were considered as having symptomatic cancers. Multivariate analyses of the risk of non-sentinel node metastases were performed including known risk factors for non-sentinel node metastases as well as method of detection. Results: 18% of the patients had metastases in non-sentinel nodes. This was evenly distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(25 reference statements)
1
0
0
Order By: Relevance
“…We observed in our study that mode of detection (screening mammography vs not) had no clear impact on finding non-SN metastases. Tvedskov et al showed in their study involving 995 patients, registered in the Danish Breast Cancer Cooperative Group (DBCG) Database, that there was no large difference in the risk of non-SN metastases between patients with clinically detected and screening detected cancers with micro-metastases or ITC in the SN [20]. In our study there was a high risk for non-SN metastases in 11 patients with unknown status for mode of detection.…”
Section: Discussionsupporting
confidence: 43%
“…We observed in our study that mode of detection (screening mammography vs not) had no clear impact on finding non-SN metastases. Tvedskov et al showed in their study involving 995 patients, registered in the Danish Breast Cancer Cooperative Group (DBCG) Database, that there was no large difference in the risk of non-SN metastases between patients with clinically detected and screening detected cancers with micro-metastases or ITC in the SN [20]. In our study there was a high risk for non-SN metastases in 11 patients with unknown status for mode of detection.…”
Section: Discussionsupporting
confidence: 43%